Avaliação de parâmetros orais em pacientes pediátricos com e sem fibrose cística: estudo caso controle - Mesquita, Lilia Viana (2023)
Background: Cystic fibrosis (CF) is an autosomal recessive genetic disease, caused by mutations in the cystic fibrosis transmembrane conductance regulator gene (CFTR), essential in regulating the flow of chloride, sodium and water. As a resulto of these defective or insufficient CFTR proteins in mucous membranes on body, these mutations alter the excretion of these electrolytes, making the secretions of various organs thicker. Thus, there is a relationship between the absence or partial functioning of the CFTR gene and the pathophysiology of CF. Patients diagnosed with CF may present the following oral changes: cavities, plaque accumulation and dental calculus, as well as salivary changes. The treatment of these patients depends on a multidisciplinary team in reference centers for CF and the presence of a Dental Surgeon is essential for the treatment of oral diseases and complications. Objective: To evaluate oral health parameters (caries index, dental plaque and gingival bleeding) in pediatric patients with and without CF. Materials and methods: An observational, cross-sectional and analytical study was carried out, with 25 patients diagnosed with CF (CF group) and 25 individuals without the disease (control group), matched by sex and age. The ICDAS caries detection method, plaque index and gingival bleeding index were used. Results: Of the 25 patients in the CF group, 13 were female and 12 were male, with an age range of 4 to 17 years and a mean age of 10.12 ± 3.35 (p = 0.564). The plaque index was higher in patients in the CF group (0.678 ± 0.219), compared to patients in the control group (0.397 ± 0.227; p < 0.001). The gingival bleeding index was also higher in the FC group (0.630 ± 0.213), when compared to individuals in the control group (0.365 ± 0.239; p < 0.001). Individuals in the CF group had a lower prevalence of caries (0.093 ± 0.113) compared to patients in the control group (0.118 ± 0.184), with no statistical difference (p = 0.852). Conclusion: Patients with CF are more susceptible to plaque accumulation, evidenced by the higher rates of plaque and gingival bleeding present in this group, and greater attention should be paid to periodontal health. The prevalence of caries in the CF group should be further investigated, as it was not significant when compared to the control group.